2009
DOI: 10.1111/j.1365-2133.2009.09467.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of matrix metalloproteinase expression and activity in atopic dermatitis using a novel skin wash sampling assay for functional biomarker analysis

Abstract: A simple skin wash technique suitable for the quantitative and functional analysis of biomolecules in AD is described. Using this method we show that MMPs, and in particular MMP-8 and MMP-9, represent an important potential component of the pathology of AD. The method is expected to prove useful in advancing our understanding of AD and in identifying biomarkers for the evaluation of new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 49 publications
6
65
0
Order By: Relevance
“…Up-regulation of MMP-9 expression in the inflamed area of the skin may lead to the degradation of extracellular matrix proteins, resulting in increased infiltration of immune cells into the skin. Previous studies have shown that the activity of MMPs such as MMP-9 is increased in skin wash samples from AD lesions (6). ROS is considered to play a major role in inflammation processes during the development of inflammatory skin diseases (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up-regulation of MMP-9 expression in the inflamed area of the skin may lead to the degradation of extracellular matrix proteins, resulting in increased infiltration of immune cells into the skin. Previous studies have shown that the activity of MMPs such as MMP-9 is increased in skin wash samples from AD lesions (6). ROS is considered to play a major role in inflammation processes during the development of inflammatory skin diseases (21).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 can mediate the degradation of extracellular matrix proteins such as type IV collagen during the inflammatory response. It has been implied that dysregulation of MMP activity is associated with inflammatory skin diseases such as atopic dermatitis (AD) (5,6). Previous studies reported that elevated levels of MMP-9 are present in the plasma of patients with AD (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite recently, Harper et al have revealed that the activity of MMPs in skin lesions associated with atopic dermatitis is approximately five-fold higher than in unaffected regions and as many as 10 to 24 times higher than in the healthy individuals. Furthermore, elevated levels of MMP-8 and MMP-9 were documented in atopic dermatitis patients, while the levels of MMP-10, TIMP-1, and TIMP-2 were markedly lower than in healthy individuals [27]. Also, Devillers et al observed an elevated serum level of MMP-9 in atopic dermatitis patients as compared to a group of healthy individuals [28].…”
Section: A At To Op Pi Ic C D De Er Rm Ma At Ti It Ti Is Smentioning
confidence: 97%
“…Atopic dermatitis is a major degenerative disease, which presents as a chronic inflammatory skin condition with a deficiency in barrier function (16). It is now well recognized that several proteases, including the matrix metalloproteinases (MMPs), play key roles in the immunopathology of and biological functions during progression of the disease (17).…”
Section: Introductionmentioning
confidence: 99%